2022
DOI: 10.7759/cureus.27411
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy and Trauma: The Role of Injuries as Physical Stressors

Abstract: Introduction: Physical stressors are common predisposing factors for takotsubo cardiomyopathy (TTC). However, the role of traumatic injuries in TTC has not been well defined. This study describes the characteristics of TTC in the broad spectrum of traumatic injuries using the information available in the National Trauma Data Bank (NTDB).Materials and methods: This retrospective study analyzed trauma patients ≥ 18 years old in the NTDB, from 2007 to 2018, with a diagnosis of TTC.Results: A total of 95 TTC diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Onset following a stressful event, as is resolution of apical wall akinesis within days to weeks [ 1 , 4 ]. Physical trauma has also been documented as a precipitating event to TTC [ 5 ]. Researchers found that 0.001 % of the patients who developed TTC following a physical trauma were most commonly elderly females after a blunt traumatic injury [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onset following a stressful event, as is resolution of apical wall akinesis within days to weeks [ 1 , 4 ]. Physical trauma has also been documented as a precipitating event to TTC [ 5 ]. Researchers found that 0.001 % of the patients who developed TTC following a physical trauma were most commonly elderly females after a blunt traumatic injury [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physical trauma has also been documented as a precipitating event to TTC [ 5 ]. Researchers found that 0.001 % of the patients who developed TTC following a physical trauma were most commonly elderly females after a blunt traumatic injury [ 5 ]. We present a case of an elderly female who suffered TTC after a motor vehicle collision.…”
Section: Introductionmentioning
confidence: 99%